2016
DOI: 10.2500/ajra.2016.30.4364
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Products to Treat Allergic Rhinitis and Alternative Routes for Allergy Immunotherapy

Abstract: There are alternative routes and products to improve the efficacy of immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Since the 1990s, CP has gained extensive clinical application in the preventative management of AR and hay fever worldwide [15, 16]. However, few studies have directly explored the impact of CP on mucociliary clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, CP has gained extensive clinical application in the preventative management of AR and hay fever worldwide [15, 16]. However, few studies have directly explored the impact of CP on mucociliary clearance.…”
Section: Discussionmentioning
confidence: 99%
“…[8,22]. The use of black cumin oil in suppressing allergic reactions is associated with the probable antihistamine properties of the oil and the inhibition of enzymes responsible for the metabolism of arachidonic acid [23,24].…”
Section: Advances In Engineering Research Volume 151mentioning
confidence: 99%
“…Further, numerous studies have shown that neuroendocrine immunity (NEI) plays a important role in AR [25,26] and acupuncture may affect the function of the NEI system to treat AR. [13,[27][28][29].…”
mentioning
confidence: 99%